208k views
5 votes
Hard question!!!please help me !
there is english below ​

Hard question!!!please help me ! there is english below ​-example-1

1 Answer

10 votes

9514 1404 393

Answer:

t = ±√3

Explanation:

The first equation tells us ...

x^2 +tx +2 = (x -h)(x -k)

x^2 +tx +2 = x^2 -(h+k)x +hk

Comparing coefficients, we have the equations ...

t=-(h+k)

2 = hk

__

The second equation tells us ...

2x^2 +mx +2m = 2(x -h/k)(x -k/h)

2x^2 +mx +2m = 2x^2 -2(h/k +k/h)x +2

Comparing coefficients, we have the equations ...

m = -2(h/k +k/h)

2m = 2

__

Dividing the last equation by 2 gives ...

m = 1

Using that in the third equation, we have ...

1 = -2(h/k +k/h) = -2(h^2 +k^2)/hk

Using hk = 2, this gives us ...

h^2 +k^2 = -1

From the first equation, we know ...

t^2 = (-(h+k))^2 = h^2 +2hk +k^2 = (h^2 +k^2) +2(hk)

Substituting the values for these terms, we have ...

t^2 = -1 + 2(2) = 3

t = ±√3

Possible values of t are √3 and -√3.

User Cosmin Onea
by
5.0k points